Gendered reading gendered readers : responding to drama from a gendered perspective - Collin, Jerome (Proceedings of the Science and Art of Language in Teaching (SALT) International Conference, Penang, Malaysia., 2006)
From the ancient to contemporary times, drama has communicated and conveyed the messages as well as representations of gender and sexuality through the elements such as dialogue and characters. It has constantly (re)defined and (re)constructed the representations of gender and sexuality which has affected readers’/audience’s awareness and understanding of their own gender and sexuality. Thus, this study explores readers’ views on the representation of gender in drama, and how this representation reflects and affects their awareness and understanding of gender. This takes into account reading drama as a gendered act that engages readers to read from their gendered perspectives. In view of this, the study examines a) readers’ views on the representation of characters as gendered beings in selected dramatic texts, b) the effects that this representation has on their awareness and understanding of their own gender, and c) the extent to which reading from a gendered perspective helps them better understand the characters as gendered beings. Questionnaires were distributed to 72 Unimas TESL and ESL undergraduates, followed by a series of interviews to elicit their views on the aspects that the study seeks to examine. The findings show that both male and female respondents invariably responded to the representation of gendered characters which subsequently influenced their understanding of gender in general and their own gender in particular. The findings also reveal the contrasts in their construction of gender identity which was influenced by the stereotyped and non-stereotyped beliefs about gender. Additionally, reading the dramatic texts from a gendered perspective had influenced their views on the characters’ as gendered beings. It is hoped that the study will shed more insights into the effects that gender portrayals in literary texts have on adult readers’ understanding of gender which takes into account reading literary texts from a gendered perspective. Hence the importance to instigate gender awareness and gender equity in the literature classroom.